Associations between clinical features and therapy with macrophage subpopulations and T cells in inflammatory lesions in the aorta from patients with Takayasu arteritis. (30th July 2020) - Santos, J P; Artigiani Neto, R; Mangueira, C L P; Filippi, R Z; Gutierrez, P S; Westra, J; Brouwer, E; de Souza, A W S
Summary: Takayasu arteritis (TAK) is a large-vessel granulomatous vasculitis; the inflammatory infiltration in arteries comprises macrophages, multi-nucleated giant cells, CD4 + and CD8 + T cells, γδ T cells, natural killer (NK) cells and neutrophils. However, it is unknown which subtype of macrophages predominates. This study aims to evaluate macrophages subpopulations in the aorta in TAK. Immunohistochemistry was performed in the aorta from TAK patients ( n = 22), patients with atherosclerotic disease ( n = 9) and heart transplant donors ( n = 8) using the markers CD68, CD86, CD206, CD3, CD20 and CD56. Active disease was observed in 54·5% of patients and active histological lesions were found in 40·9%. TAK patients presented atherosclerotic lesions in 27·3% of cases. The frequency of macrophages, M1 macrophages, T, B and NK cells was higher in the aorta from TAK and atherosclerotic patients compared to heart transplant donors. In TAK, macrophages and T cells were the most abundant cells in the aorta, and the expression of CD206 was higher than CD86 ( P = 0·0007). No associations were found between the expression of cell markers and active disease or with atherosclerotic lesions. In TAK patients, histological disease activity led to higher T cell counts than chronic fibrotic lesions ( P = 0.030), whereas prednisone use was associated with lower T cell counts ( P = 0·035). In conclusion, M1 macrophages were more frequent in TAK and atherosclerotic patients compared to heart transplant donors, while M2 macrophages dominated M1 macrophages in TAK. T cells were associated with histological disease activity and with prednisone use in TAK. Graphical Abstract: